Evaluasi Sistem Pemerintahan Berbasis Elektronik Menggunakan E-Government Maturity Model (Kasus di Pemerintah Kota Gorontalo) - Abdul Aziz Bouty; Mohammad Hidayat Koniyo; Dian Novian (BPSDMP Kominfo Manado, 2019)
Utilization of information and communication technology in the implementation of the current government process is a priority scale that needs to be continuously developed by the government. In its implementation there is a problem that is the lack of an evaluation process carried out, especially at the level of local government towards the use of information and communication technology. The purpose of this research is to evaluated of an electronics based governance system by measuring the maturity level. Measuring the maturity level on the technical function capability using e-government maturity models and assessing 3 domains, 7 aspects and 35 indicators contained in an electronic based governance system. The research method used is survey method, in the environtment of government of Gorontalo City. The results of this research showed that the implementation of an electronic based government system in the government of Gorontalo City achieve “GOOD” predicate with a total index value of 2.88. Some indicators that have the lowest indeks value from the measurement and assessment results are informed in this study to further become recommendations for improvement the utilization of information and communication technology by the government of Gorontalo City.Keywords : evaluation, information technology, public service, maturity level.